Groups which are isomorphic to their subgroups with non-modular subgroup lattice - De Falco, M.; Musella, C. (Algebra and Discrete Mathematics, 2006)
This paper describes the structure of groups G containing proper subgroups with non-modular subgroup lattice and such that all such subgroups are isomorphic to G.